Ecological insights on the feeding behaviour of waterbirds in an Important Bird and Biodiversity Area of South West Johor Coast, Malaysia - Nur Athirah Fauzi; Kaviarasu Munian; Nur Aina Amira Mahyudin; Nor Atiqah Norazlimi (Biodiversity Data Journal)
Mangroves and mudflats are essential intertidal habitats that support benthic communities, providing critical feeding grounds for waterbirds. However, the degradation of these habitats due to coastal reclamation poses significant threats to prey availability and waterbird populations along the South est Johor Coast. While most avian research in Johor focuses on forest birds, studies on coastal waterbirds, particularly their feeding ecology, remain scarce. Understanding the feeding ecology of waterbirds is crucial for strengthening conservation efforts in vulnerable intertidal habitats. This study investigated the feeding behaviour and diet composition of waterbirds along the South West Johor Coast, Malaysia. Fieldwork was conducted in three coastal mudflats from November 2020 to May 2021, employing the direct observation technique. A total of 576 hours of observation were recorded, averaging 2 hours and 19 minutes per focal observation. Of 17 waterbird species recorded, only 11 species were included in the analysis based on sufficient data. The results revealed that waterbirds primarily consumed fish, molluscs, worms, crabs and unidentified prey, with fish comprising 25% of their overall diet. Feeding behaviour varied significantly by morphology traits, with larger waterbirds demonstrating higher feeding efficiency. Despite lower feeding rates and shorter feeding durations, larger species had a greater percentage of successful feeding attempts, indicating their superior ability to meet energy requirements. These findings provide crucial baseline data for understanding waterbird feeding ecology and highlight the importance of conserving the intertidal habitats. This research contributes to the development of targeted conservation strategies for waterbirds in the Important Bird and Biodiversity Area (IBA) of the South West Johor Coast, Malaysia, an area increasingly at risk from habitat degradation.